Skeletal metastases and pathological fractures of long bones - Rajković, Stanislav; Mičeta, Lazar; Simić, Ljubica; Djuričić, Goran; Baščarević, Zoran; Lujić, Nenad; Sopta, Jelena (Medical Research, 2022)
Introduction. The most common cause of pathological fractures are skeletal metastases. Ten percent of patients with diagnosed skeletal metastases will sustain a pathological fracture. Skeletal metastases can be treated by non-surgical methods, including analgesics, bisphosphonates, and radiotherapy, with the primary goal of pain relief and slowing down tumor growth. Surgical treatment is indicated for impending or existing fractures. It includes stabilization with internal fixation using various nails, plates, and screws with or without osteoplasty, and endoprosthetic joint replacement, especially in lesions around major joints – hip, knee, and shoulder.Material and Methods. The study included patients operatively treated at the Institute for orthopaedics “Banjica” and pathohistologically analyzed at the Institute for pathology in Belgrade during the one-year period from February 2021. to January 2022. Inclusion criteria were an existing or impending pathological fracture of long bones, operative treatment with tissue sampling, and consequent pathohistological diagnosis of metastatic carcinoma. Excluded from the study were patients with biopsy-proven processes other than metastatic carcinomas. The total number of patients included in the study was 69.Results. The mean age of patients at the pathological fracture occurrence was 67.7 (ranging from 42 to 88). Malignant diseases diagnosed were: breast cancer 36.1%, lung 24.5%, kidney 14.5%, prostate 13.1%,  colorectal 2.9%, other (8.9%). The radiological presentation was in the form of lysis in 75.4% and blastic in 24.6%. Operative treatment included arthroplasty in 53.6% of patients and stabilization with nail or plate in 46.4%.Conclusion. Pathological fractures represent the final outcome of tumor activity in a bone and cause significant suffering in patients expressed through severe pain and often immobility, which accelerates all the pathological processes and leads to death. Joint methods of contemporary chemotherapy, radiotherapy, and surgery enabled significant life quality improvement and extension in these patients.
Keywords: skeletal metastases, pathological fracture, surgical therapy